Sex Trafficking: Examining Links to Prostitution and the Routine Activity Theory - Kenyon, Samuel; Schanz, Youngyol (International Journal of Criminology and Sociology, 2014)
Sex trafficking is often a concern in international communities. However, sex trafficking victims do not always cross international boarders; these victims can be trafficked within their own countries. The purpose of the study is to examine the perceptions of law enforcement agents experienced in investigations of prostitution and sex trafficking incidents. Qualitative data were collected by interviewing law enforcement agents along the east coast region of the United States. An analysis of the interview data uncovered a series of themes which include desire for money, drug activity, lack of awareness, and varying tolerance levels. The research results were applied to the framework of routine activity theory (Cohen &Felson, 1979). It was found that the three elements (motivated offenders, suitable targets, and absence of a capable guardian) of the theory were well applied to describe sex trafficking activity. Important future research implications as well as policy implications were discussed.